Faktor determinan dan disparitas kesehatan gigi dan mulut anak di wilayah perkotaan dan perdesaan: A systematic review - Razin Alifahrezy Setyaliani; Dwi Sarwani Sri Rejeki; Suratman Suratman (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Oral health problems during childhood can have long-term impacts on oral health in adulthood, negatively impacting children's general health and academic achievement. Furthermore, children's oral health is influenced by various determinants and shows differences between urban and rural areas. Purpose: To analyze the determinants and disparities in oral health among children in urban and rural areas. Method: This systematic review used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to analyze and evaluate research findings identified through a literature search in PubMed and Google Scholar using the keywords